Development of Job Sheet in Technical Drawing Subject to Improve Drawing Competency of Grade X Students Vocational School - Rio Farkhan; Widodo Widodo; Arif Bintoro Johan (Journal of Education Technology, 2025)
This study was motivated by the low level of student competency in technical drawing practice, as indicated by suboptimal learning outcomes, limited conceptual understanding, and confusion during practical sessions using conventional learning modules. These conditions have made the learning process less effective and efficient and have reduced students’ motivation due to frequent drawing errors. This research aims to develop and evaluate the feasibility of a technical drawing job sheet as a learning medium to enhance students’ drawing competency in vocational education. The research employed a Research and Development (R&D) design based on the Borg and Gall model, which includes the stages of define, design, develop, and disseminate. The subjects involved were grade X students in the light vehicle engineering program. Data were collected through expert validation questionnaires and student response surveys, and analyzed using quantitative descriptive statistics. The findings indicate that the developed technical drawing job sheet meets the criteria of high feasibility, based on expert assessments and positive student responses. The implications of this study highlight that the use of the job sheet can enhance learning effectiveness, foster learner autonomy, and increase students’ interest in technical drawing activities.